Statin therapy modulates thickness and inflammatory profile of human epicardial adipose tissue. (1st January 2019) - Parisi, Valentina; Petraglia, Laura; D'Esposito, Vittoria; Cabaro, Serena; Rengo, Giuseppe; Caruso, Aurelio; Grimaldi, Maria Gabriella; Baldascino, Francesco; De Bellis, Antonio; Vitale, Dino; Formisano, Roberto; Ferro, Adele; et al.
Abstract: Background: Epicardial adipose tissue (EAT) thickness and pro-inflammatory status has been shown to be associated with several cardiac diseases, including aortic stenosis (AS). Thus, cardiac visceral fat could represent a potential new target for drugs. In the present study we evaluate the effect of statin therapy on EAT accumulation and inflammation. Methods: Echocardiographic EAT thickness was assessed in 193 AS patients taking (n.87) and not taking (n.106) statins, undergoing cardiac surgery. To explore the association between statin therapy and EAT inflammation, EAT biopsies were obtained for cytokines immunoassay determination in EAT secretomes. An in vitro study was also conducted and the modulation of EAT and subcutaneous adipose tissue (SCAT) secretomes by atorvastatin was assessed in paired biopsies. Results: Statin therapy was significantly associated with lower EAT thickness (p < 0.0001) and with lower levels of EAT-secreted inflammatory mediators (p < 0.0001). Of note, there was a significant correlation between EAT thickness and its pro-inflammatory status. In vitro, atorvastatin showed a direct anti-inflammatory effect on EAT which was significantly higher compared to the SCAT response to statin incubation (p < 0.0001). Conclusions: The present study indicates a robust association between statin therapy and reduced EAT accumulation in patients with AS. The present data also suggest a direct relationship between EAT thickness and its inflammatory status, both modulated by statin therapy. The in vitro results support the hypothesis of a direct action of statins on EAT secretory profile. Overall our data suggest EAT as a potential new therapeutic target for statin therapy. Highlights: Statin therapy is associated with a reduced EAT thickness. The association between statins and EAT is paralleled by an attenuation of EAT inflammatory profile. Statins have a direct and selective anti-inflammatory effect on EAT.